2015
DOI: 10.1039/c5tc00835b
|View full text |Cite
|
Sign up to set email alerts
|

An in situ SERS study of substrate-dependent surface plasmon induced aromatic nitration

Abstract: Here we demonstrate the surface plasmon (SP) induced nitration of aromatic rings by an in situ surface enhanced Raman spectroscopy (SERS) technique. The size feature of the as-prepared Au, Ag and Ag@PDA@Au hierarchical structures allows monitoring the entire reaction process on a single hierarchical structure. With benzenethiol (BT) and HNO 3 as reactants, SP induced aromatic nitration can be successfully realized without the assistance of a conventional acid catalyst, H 2 SO 4 . Experimental and theoretical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 44 publications
0
15
0
1
Order By: Relevance
“…In 2015, Huang et al reported an in situ SERS study of substrate-dependent surface plasmon-induced aromatic nitration. [65] In the absence of a conventional acid catalyst (H 2 SO 4 ), pNTP was successfully synthesized by surface plasmon-induced nitration of benzenethiol using HNO 3 . This SP-induced chemical reaction also showed substrate-dependent reaction kinetics, proceeding more rapidly on Au surfaces than on Ag.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, Huang et al reported an in situ SERS study of substrate-dependent surface plasmon-induced aromatic nitration. [65] In the absence of a conventional acid catalyst (H 2 SO 4 ), pNTP was successfully synthesized by surface plasmon-induced nitration of benzenethiol using HNO 3 . This SP-induced chemical reaction also showed substrate-dependent reaction kinetics, proceeding more rapidly on Au surfaces than on Ag.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
“…Since 2010, various experimental and theoretical results have supported the production of DMAB from pATP by plasmon-driven surface-catalyzed chemical reactions. [61][62][63][64][65][66][67][68][69][70][71][72] Adv. Optical Mater.…”
Section: Hot Electron-induced Surface-catalyzed Chemical Reactionsmentioning
confidence: 99%
“…Decreasing laser energy and power and changing the polarization are known to affect the catalytic power of the plasmons, although the signal-enhancing effects of the plasmonic particles are thereby sacrificed. 29,72,81 …”
mentioning
confidence: 99%
“…In order to measure the rate of the enzymatic degradation of TCP, the SERS detector based on SK307 may be employed. The idea of reaction monitoring in situ by SERS has been widely realized [38,39]. The success of this approach would depend on the rate of fouling of the SERS substrate by the enzyme and its degradation products.…”
Section: Using the Microfluidic Sers Detector With Sk307 For Environmmentioning
confidence: 99%